Chimpanzee-Specific Endogenous Retrovirus Generates Genomic Variations in the Chimpanzee Genome - Mun, Seyoung (Public Library of Science, 2014)
Endogenous retroviruses (ERVs), eukaryotic transposable elements, exist as proviruses in vertebrates including primates and contribute to genomic changes during the evolution of their host genomes. Many studies about ERVs have focused on the elements residing in the human genome but only a few studies have focused on the elements which exist in non-human primate genomes. In this study, we identified 256 chimpanzee-specific endogenous retrovirus copies (PtERVs: Pan troglodyte endogenous retroviruses) from the chimpanzee reference genome sequence through comparative genomics. Among the chimpanzee-specific ERV copies, 121 were full-length chimpanzee-specific ERV elements while 110 were chimpanzee-specific solitary LTR copies. In addition, we found eight potential retrotransposition-competent full-length chimpanzee-specific ERV copies containing an intact env gene, and two of them were polymorphic in chimpanzee individuals. Through computational analysis and manual inspection, we found that some of the chimpanzee-specific ERVs have propagated via non-classical PtERV insertion (NCPI), and at least one of the PtERVs may have played a role in creating an alternative transcript of a chimpanzee gene. Based on our findings in this study, we state that the chimpanzee-specific ERV element is one of the sources of chimpanzee genomic variations, some of which might be related to the alternative transcripts in the chimpanzee population.